Desain Dan Pembangunan Sistem Informasi Geografis Berbasis Web Menggunakan Metode Prototype Untuk Meningkatkan Daya Tarik Wisata - Iqbal, Rifqi Muhammad; Supiyandi; Mohammad Yusup (Jurnal Mahajana Informasi, 2024)
This study aims to design and develop a web-based Geographic Information System (GIS) using the prototype method as a development approach to enhance tourism appeal. The system is designed to provide interactive, accessible, and relevant information about tourist locations, thereby supporting more effective tourism promotion. The prototype method allows for rapid design iterations between developers and stakeholders, enabling user needs to be identified and well-accommodated. The system is equipped with key features such as location search based on name or category, an interactive map supporting route navigation and location markers, as well as a responsive interface for various devices, including desktops, tablets, and smartphones. System testing was conducted using the Black Box Testing method, focusing on functionality without examining the internal structure. Testing results indicate that all key system features perform according to specifications and provide a positive user experience. Moreover, the system is capable of displaying tourist location information accurately, responsively, and attractively, thereby increasing tourists' interest in visiting. The web-based Geographic Information System developed through this research is expected to serve as an effective tool for promoting tourism and contributing positively to the growth of the tourism sector. Future development may include additional features such as user reviews, social media integration, and optimal route predictions based on real-time traffic conditions.